DIGITALIZATION OF AGRICULTURAL MECHANIZATION PROCESSES - Zokirov Sanjar Zokhidjon oglu; Kholiyarov Farhod Toshmuradovich; Mahmudov Abbas Sherali oglu; Tleubergenova Alima Alisherovna (Modern American Journals, 2025)
This article presents a comprehensive study of the methodological foundations for the digitalization of agricultural mechanization processes in Uzbekistan, with a focus on the conditions of the Surkhandarya region. The research aims to enhance the effectiveness of digitalization in agriculture by monitoring soil moisture in real-time and optimizing agro-technical parameters such as machinery speed, working depth, and equipment selection. The scientifically grounded approach, based on modern digital technologies including IoT sensors, artificial intelligence, and mobile/web applications, contributes to the efficient management of land resources and the generation of useful recommendations for farmers. The results indicate that decisions supported by automated monitoring systems lead to increased crop yields and more efficient use of resources.
Keywords: Agricultural digitization, soil moisture, agro-technical operations, artificial intelligence, IoT sensors, recommendations, mobile application, agricultural machinery, data analysis, real-time monitoring, drone observation.